Troubleshooting virtual private networks - Lewis, Mark (Cisco Press, 2004)
Master advanced troubleshooting techniques for IPSec, MPLS Layer-3, MPLS Layer-2 (AToM), L2TPv3, L2TPv2, PPTP, and L2F VPNs Learn the step-by-step, end-to-end methodology essential for troubleshooting virtual private networks (VPNs) Gain the in-depth knowledge necessary for fast and efficient troubleshooting of IPSec, MPLS Layer-3, MPLS Layer-2 (AToM), L2TPv3, L2TPv2, PPTP, and L2F VPNs Master advanced troubleshooting tools and techniques for all applicable VPN types Debug and fix IPSec site-to-site and remote access VPN issues, such as IKE (ISAKMP) phase 1 and phase 2 negotiation failure, ESP and AH traffic drops, certificate enrollment failures, and maximum transmission unit (MTU) problems Locate and resolve MPLS Layer-3 VPN problems, such as those involving route exchange and label switched path (LSP) failure, MPLS VPN over traffic engineering tunnels, and Multicast VPNs (MVPN) Discover solutions for issues in AToM and L2TPv3-based Layer-2 VPNs, including pseudowire setup failures, attachment circuit problems, and MTU issues Obtain answers for L2TPv2, PPTP, and L2F control connection establishment, session setup, PPP negotiation, and VPN performance issues Refer to specially designed flowcharts to identify issues and find solutions fast Consolidate VPN troubleshooting knowledge through bonus hands-on labs Read and understand detailed analysis of all relevant VPN show and debug command output Troubleshooting Virtual Private Networks presents a systematic troubleshooting methodology for network engineers, administrators, and architects tasked with managing and deploying Cisco IOS VPNs. With eight self-contained chapters designed to facilitate rapid and straightforward troubleshooting, this book provides detailed information on addressing all common and not-so-common issues with IPSec VPNs, MPLS Layer-3 VPNs, Any Transport over MPLS (AToM)-based Layer-2 VPNs, L2TP Version 3 (L2TPv3)-based Layer-2 VPNs, L2TP Version 2 (L2TPv2) VPNs, PPTP VPNs, and L2F VPNs. This book not only shows you how to correct problems but also how to avoid them in the first place with expert VPN configuration guidance and optimization tips. Each chapter in Troubleshooting Virtual Private Networks includes a step-by-step, end-to-end troubleshooting approach to a different VPN technology. In-depth technical discussions and configuration reviews orient you to the VPN technology and get you ready to work. To help you access the answers you need, you'll find flowcharts in ea...
Includes index
Keywords: Extranets (Computer networks); Extranets; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications